2020
DOI: 10.1002/jmri.27189
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Model for Intermediate‐Stage Hepatocellular Carcinoma Response to Transarterial Chemoembolization

Abstract: Background: The outcome of intermediate-stage hepatocellular carcinoma (HCC) treated with transarterial chemoembolization (TACE) is greatly heterogeneous. Current means for predicting HCC response to TACE are lacking. Purpose: To investigate whether the combination of parameters derived from amide proton transfer (APT) and intravoxel incoherent motion (IVIM) imaging, and morphological characteristics of tumor can establish a better prediction model than the univariant model for HCC response to TACE. Study Type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
(74 reference statements)
0
12
0
Order By: Relevance
“…This promising model was shown to be associated with recurrence‐free survival 30 . Another avenue of research is evaluating advanced quantitative methods such as intravoxel incoherent motion MRI focusing on the metabolic function of tumoral tissue 31 . Finally, like in most medical fields, machine learning is now being evaluated in predicting the response to TACE.…”
Section: Examples Of Advances As a Results Of Quantitative Models For Hepatocellular Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…This promising model was shown to be associated with recurrence‐free survival 30 . Another avenue of research is evaluating advanced quantitative methods such as intravoxel incoherent motion MRI focusing on the metabolic function of tumoral tissue 31 . Finally, like in most medical fields, machine learning is now being evaluated in predicting the response to TACE.…”
Section: Examples Of Advances As a Results Of Quantitative Models For Hepatocellular Carcinomamentioning
confidence: 99%
“…30 Another avenue of research is evaluating advanced quantitative methods such as intravoxel incoherent motion MRI focusing on the metabolic function of tumoral tissue. 31 Finally, like in most medical fields, machine learning is now being evaluated in predicting the response to TACE. One published study attempted to evaluate the performance of a CT-based neural network with encouraging results.…”
Section: Prognosis and The Assessment Of Treatment Responsementioning
confidence: 99%
“…Among the 33 studies, 11 investigated IVIM for HCC diagnosis, namely for HCC detection respect to normal liver parenchyma or other types of hepatic lesions (either benign or malignant), and seven evaluated the power of IVIM parameters for HCC histological grading. Among the 15 remaining studies, six assessed the usefulness of IVIM for the response of HCC to therapy [40,42,48,66,69,73], five evaluated if IVIM could be associated with prognostic factors [51,52,56,58,67], and four explored IVIM model for multiple aims [37,41,53,64] (two investigated response to therapy and survival [53,64], one on grading and prognostic factors [41], and the remaining one on diagnosis and grading [37]).…”
Section: Studies On Ivimmentioning
confidence: 99%
“…Among studies assessing the usefulness of IVIM the response of HCC to therapy, Jia et al [40] found that D could be helpful in predicting HCC response to transarterial chemoembolization (TACE) and was a significant predictor of response to therapy both univariately and in multivariate analysis, including also parameters derived from amide proton transfer. Park et al [73] also assessed the usefulness of IVIM in the response of TACE in HCC and found that D* was able to distinguish patients with good lipiodol uptake from those with a poor one.…”
Section: Response To Therapymentioning
confidence: 99%
“…Therefore, a fast image readout was chosen, such as echo planar imaging (EPI), rapid imaging with refocused echoes (RARE), fast spin echo (FSE), and/or fast imaging with steady-state precession (FISP) [ 6 , 34 , 35 , 36 ]. As shown in Table 1 , out of the three papers on liver and the two on lung, four used FSE [ 74 , 75 , 81 , 82 ] and one used EPI [ 73 ]. Besides a fast readout, respiration-gated design [ 81 , 82 ] or breath holding [ 73 , 74 ] are still required to reduce motion during acquisition.…”
Section: Technical Issues For Non-brain Tumor Imagingmentioning
confidence: 99%